2016
DOI: 10.1007/s12328-016-0646-7
|View full text |Cite
|
Sign up to set email alerts
|

Infection with fully mature Corynosoma cf. validum causes ulcers in the human small intestine

Abstract: Corynosoma is a parasite that can normally be found in the intestinal tract of fish-eating mammals, particularly in seals and birds. The present case proposed that Corynosoma could attain full maturity in the human intestine. A 70-year-old female complained of abdominal pain. A computed tomography (CT) scan revealed a swelling of the intraperitoneal lymph nodes with no responsible lesion. Video capsule endoscopy and double-balloon endoscopy detected several ulcerations and one parasite in the ileum, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…However, recent reports of human corynosomiasis from Japan showed that intestinal adults can reach sexual maturity (i.e. laying eggs), suggesting humans to be a suitable final host (Fujita et al., 2016 ; Takahashi et al., 2016 ). The species composition of Corynosoma in fish varies according to sea areas with C. strumosum tending to be the primary species (Sinisalo & Valtonen, 2003 ).…”
Section: Fish‐borne Zoonotic Parasitesmentioning
confidence: 99%
“…However, recent reports of human corynosomiasis from Japan showed that intestinal adults can reach sexual maturity (i.e. laying eggs), suggesting humans to be a suitable final host (Fujita et al., 2016 ; Takahashi et al., 2016 ). The species composition of Corynosoma in fish varies according to sea areas with C. strumosum tending to be the primary species (Sinisalo & Valtonen, 2003 ).…”
Section: Fish‐borne Zoonotic Parasitesmentioning
confidence: 99%
“…Route of infection. Ingestion of cystacanths in infected fish paratenic host ( Takahashi et al 2016 ).…”
Section: Checklist Of Eukaryotic Human Parasitesmentioning
confidence: 99%
“…The single case was reported from Japan as Corynosoma cf. validum based on DNA sequencing ( Takahashi et al 2016 ).…”
Section: Checklist Of Eukaryotic Human Parasitesmentioning
confidence: 99%
“…Many acanthocephalan species are known to have low host specificity but fortunately, for ecological reasons, are not likely to be ingested by man [11] . Man was reported to be infected with at least nine acanthocephalan species, among them, Macracanthorhynchus hirudinaceus and Moniliformis moniliformis are the most common species [12,13] . Most reported cases of acanthocephaliasis have involved the gastrointestinal tract.…”
Section: Human Acanthocephaliasismentioning
confidence: 99%